(untitled) (SOMTU Journal of Business and Management Research, 2025)
This study examines Florida’s 2022 House Bill 1467 (often called the “book ban” policy) and assesses its impacts on K-12 education. It aims to understand how the law’s design influences educational access, equity, and resource use, and how stakeholders interpret its mandates. We apply two theoretical frameworks: Lowi’s policy typology to classify the bill’s type and expected political implications, and sensemaking theory to analyze how educators, librarians, and parents interpret and enact it. Our analysis of legislative documents and expert commentary focuses on the policy’s effectiveness, feasibility, equity, cost, and efficiency. Major findings indicate that HB 1467 functions as a regulatory policy imposing extensive review processes. However, these requirements introduce significant administrative burdens. Observers describe the resulting compliance process as “costly and time-consuming,” which undermines feasibility and efficiency. The law’s broad criteria lead to varied interpretations, highlighting sensemaking challenges. We find that such complexity risks uneven implementation and may restrict student access to diverse materials, raising equity concerns. In conclusion, while the policy aims to increase parental oversight, its design may undermine efficient and equitable implementation. The study suggests clearer guidelines and support are needed to align implementation with educational goals. These findings have broader implications for designing education policies that balance stakeholder input with clarity and fairness.